Depression, anxiety and stress among metastatic breast cancer patients on chemotherapy in China - Yi-Qiang Guo; Qing-Mei Ju; Miaoning You; Yang Liu; Azlina Yusuf; Lean Keng Soon (BMC, 2023)
Abstract Objective This study aimed to assess the level of depression, anxiety and stress among metastatic breast cancer (MBC) patients undergoing chemotherapy (CT) in Beijing, China. Methods A cross-sectional study was conducted on 176 MBC women receiving CT, selected by purposive sampling. Data were collected using self-administered questionnaires that included participants' socio-demographic status, DASS-21 and Brief COPE. Data were analyzed using descriptive statistics and general linear regression analysis. Results The incidence of depression, anxiety and stress among MBC women were 52.3%, 60.2% and 36.9%, respectively. General linear regression showed that age, marital status, monthly income, physical functioning, emotional functioning, pain, dyspnea, and appetite loss were associated with depression. All variance determined the depression (R2) was 35.6%. Marital status, self-blame and behavioral disengagement were the predictors of stress and accounted for a 35.4% stress variance in MBC women. Conclusion Our study demonstrated depression, anxiety, and stress prevalence are high in MBC women. Assessment of psychological distress (depression, anxiety, and stress) is important to recognise MBC patients who need help and further medical and mental help support. This study's findings can increasingly highlight that depression, anxiety, and stress are substantial problems in MBC patients. Therefore, psychological interventions are needed to reduce depression, anxiety, and stress for MBC patients.